2018
DOI: 10.22547/ber/10.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital, Entrepreneurial Strategy and New Ventures Performance: Mediating Role of Competitive Advantage

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 78 publications
3
87
1
1
Order By: Relevance
“…Both the cost leadership strategy and differentiation strategy (hereafter referred to as entrepreneurial strategy) were found to be significantly and positively related to new venture performance (Teeratansirikool et al 2013). Especially in emerging economies such as Pakistan, entrepreneurial strategy plays a significant role in the competitiveness and success of newly established ventures (Anwar et al 2018a). Similarly, some other studies also concluded that competitive strategy (entrepreneurial strategy) has a positive and significant impact on the firm's performance (Lechner and Gudmundsson 2014;Acquaah and Agyapong 2015;Sun et al 2016).…”
Section: Competitive Advantagementioning
confidence: 95%
See 1 more Smart Citation
“…Both the cost leadership strategy and differentiation strategy (hereafter referred to as entrepreneurial strategy) were found to be significantly and positively related to new venture performance (Teeratansirikool et al 2013). Especially in emerging economies such as Pakistan, entrepreneurial strategy plays a significant role in the competitiveness and success of newly established ventures (Anwar et al 2018a). Similarly, some other studies also concluded that competitive strategy (entrepreneurial strategy) has a positive and significant impact on the firm's performance (Lechner and Gudmundsson 2014;Acquaah and Agyapong 2015;Sun et al 2016).…”
Section: Competitive Advantagementioning
confidence: 95%
“…In response to this, numerous studies have been conducted in developing and developed countries. In other words, some of the studies have focused on the factors that may cause the failure of enterprises while others have discussed the success, growth, and performance (e.g., Ahlstrom 2010;Yang et al 2018;Anwar et al 2018a). However, the growth and success of newly established ventures are relatively low in emerging economies as compared to more developed, often Western ones.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these objectives (e.g., high profit and a long-term survival), firms invest a massive amount of money in tangible and intangible resources [17]. However, recent studies have pointed out that investment in intangible resources-especially in IC-spurs SCP in emerging firms [4,18]. IC encompasses structural capital, human capital, and relational capital that might give a high return to business firms [19].…”
Section: Intellectual Capital and Sustainable Competitive Performancementioning
confidence: 99%
“…Moreover, Xu and Wang [21] confirmed that all the dimensions of IC-structural capital, human capital, and relational capital-significantly and positively enhance sustainability, financial performance, and economic growth in the business sector. Especially SMEs, due to a lack of resources and capabilities, can acquire a great advantage of IC, as it is considered less risky and a convenient resource [18]. Top managers are required to intensify initiative to encourage the promotion of IC (human capital, structural capital and relational capital) inside organizations to acquire competitive advantage [22].…”
Section: Intellectual Capital and Sustainable Competitive Performancementioning
confidence: 99%
“…Competitive advantages can be created through innovation, efficiency, quality, and customer responsiveness [19]. In an intense editor@iaeme.com market, competitive advantage is necessary for SMEs operation, especially in the emerging market, to sustain high performance [20].…”
Section: Literature Reviewmentioning
confidence: 99%